Improving photostability and efficiency of polymeric luminescent solar concentrators by PMMA/MgO nanohybrid coatings. Issue 3 (19th February 2017) - El-Bashir, S. M.; Yahia, I.S.; Al-Harbi, F.; Elburaih, H.; Al-Faifi, F.; Aldosari, N. A.
ABSTRACT: MgO nanocrystals were synthesized and doped with different concentrations in poly(methylmethacrylate) (PMMA) to prepare hybrid organic-inorganic coatings based on polymer nanohybrid thin films. The nanoparticles were found to be spherical with 62 nm diameter as determined by X-ray diffraction (XRD) and atomic force microscope (AFM). The coatings were characterized by spectroscopic tools such as optical absorption, transmission and fluorescence spectroscopy. The prepared nanohybrid films were spin-coated on cost-effective luminescent PMMA substrates doped with highly efficient luminescent dyes luminescent solar concentrators (LSCs). The outdoor photostability tests demonstrated enhanced protection against UVA radiation for coated LSCs compared to bare LSC substrates. The current–voltage characteristics of commercially produced LSC prototypes showed that the poor UV response of monocrystalline silicon solar cell can be improved by for LSCs coated by PMMA/MgO nanohybrid films which act as luminescent down shifting layer (LDSL).